Infecção pelo vírus da Imunodeficiência Humana (HIV): uma proposta de sequência de ensino investigativa para a construção do conhecimento sociocientífico e educação sexual no ambiente escolar - Lyra da Matta Machado Lana (2024)
The school serves as a setting where diverse cultures converge and interact, leading to the formation of school culture. School culture evolves through relationships and experiences within the educational environment, while scientific culture can be defined as a set of attitudes, investigative practices, and the sharing of knowledge related to natural phenomena. Through Inquiry-Based Science Education (IBSE), it becomes feasible to integrate science into the educational context, fostering practices that contribute to the scientific literacy of students. Additionally, employing the Science-Technology-Society-Environment (STSE) approach in science education enables the promotion of students' ability to make decisions in the face of specific problems, within a historical context, thereby fostering critical thinking and civic education. Given the current epidemiological data highlighting youth as the most affected group by AIDS, the importance of school-based sexual education is emphasized. In this regard, the aim of this research was to develop, implement, and reflect upon an Investigative Teaching Sequence (ITS) on human immunodeficiency virus (HIV) infection, facilitating access to information and awareness among High School students in a public school in Belo Horizonte regarding the issue. Through the application of the ITS, discussions on social, ethical, and moral issues affecting youth were initiated, leading to the construction of knowledge for the prevention of sexually transmitted infections, including AIDS. Furthermore, the establishment of a classroom environment in which students were encouraged to: "think, considering the structure of knowledge (Stage 1); express their ideas, presenting their arguments and acquired knowledge (Stages 2 and 3); critically analyze what they read (Stage 2 - text analysis); and write with clarity and authenticity (Stage 4 - digital content production and publication on Instagram)." The pedagogical mediation of the teacherresearcher throughout the ITS stages is noteworthy, fostering dialogues with and among students, utilizing the using HIV infection and AIDS as a central issue. Through teacherstudent and student-student interactions, the development of IBSE as a social practice of transformation was achieved, contributing to sexual education, and promoting more active and autonomous student involvement in the science teaching and learning process.